2007
DOI: 10.1111/j.1479-828x.2007.00716.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of continuous glucose monitoring in clinical decision‐making in diabetes in pregnancy

Abstract: CGMS is a well-tolerated clinically useful tool in the management of gestational diabetes and pre-existing diabetes in pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 35 publications
1
54
0
Order By: Relevance
“…CGM can also be used as an adjunct to BGM to monitor nocturnal hypoglycemia and hyperglycemia, as well as the peak and duration of postprandial hyperglycemia. A 2007 clinical trial of CGM in pregnancy reported that the additional information provided by CGM altered clinical management decisions in 62% of cases (this trial did not evaluate patient outcomes) (121). Table A3 in Appendix A of this document summarizes pivotal trials of BGM and CGM in patients with pregnancy complicated by diabetes.…”
Section: Pregnancy Complicated By Diabetesmentioning
confidence: 99%
“…CGM can also be used as an adjunct to BGM to monitor nocturnal hypoglycemia and hyperglycemia, as well as the peak and duration of postprandial hyperglycemia. A 2007 clinical trial of CGM in pregnancy reported that the additional information provided by CGM altered clinical management decisions in 62% of cases (this trial did not evaluate patient outcomes) (121). Table A3 in Appendix A of this document summarizes pivotal trials of BGM and CGM in patients with pregnancy complicated by diabetes.…”
Section: Pregnancy Complicated By Diabetesmentioning
confidence: 99%
“…In the study by McLachlan and colleagues, 98 the majority of respondents reported that the CGMS was either 'very easy to use' or 'easy to use' (n = 44, 92%), the level of inconvenience was 'minimal' or 'minor' (n = 39, 81%), their understanding of how they could control blood glucose was either 'clearly better' or 'better' (n = 43, 90%) and they felt that the benefits of the CGMS outweighed the inconvenience (n = 37, 77%). In a study of 9 days of continuous CGMS 81 use in 22 patients, 9% reported sleep disturbances, 5% attention deficits, 18% discomfort related to the sensor, 27% discomfort related to the adhesive tape and 23% technical monitor-related problems.…”
Section: The User Perspectivementioning
confidence: 99%
“…A total of 21 studies 31,41,43,49,50,53,55,56,59,74,79,81,82,84,87,89,90,[95][96][97][98] report on some aspect of the user's perspective on the various continuous glucose monitoring devices. The majority of these studies limited their assessment of the user perspective to either anecdotal or subjective reports on the part of the investigator.…”
Section: The User Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…However, women with type 1 diabetes mellitus (T1DM) treated with multiple daily injections (MDI) throughout pregnancy experience prolonged daily exposure to higher than recommended glucose levels, resulting in a 3-5-fold greater incidence of complications than that observed in the general population [11]. Some studies have shown that improvements in HbA 1c levels achieved with MDI are associated with an increased risk of severe hypoglycemia, particularly nocturnal and undetected postprandial hyperglycemia [16][17][18]. Severe hypoglycemia affects 25-40% of pregnant women and is 3-5 times more common in early pregnancy than in the period before pregnancy [18,19].…”
Section: Introductionmentioning
confidence: 99%